Decolorization of Treated Municipal Wastewater for Non-Potable Reuse Using a Household UV/H2O2 Process: 10.32526/ennrj/24/20250159 - Phumphuang, Chanoknan; Manoonpong, Kwannate; Jiemvarangkul, Pijit (Environment and Natural Resources Journal, 2025)
Color remaining in treated municipal wastewater can limit its acceptance for non-potable reuse. This study evaluated a simple UV/H2O2 step for decolorization of secondary effluent from three Bangkok Metropolitan Administration (BMA) wastewater treatment plants. Experiments were performed in a 0.75 L batch reactor equipped with a single low-pressure UV lamp (254 nm, 16 W); H2O2 doses of 33, 100, 167, and 333 mg/L were tested at ambient 25-30°C and unadjusted pH. Reaction times were 0-10 minutes with sampling at 0, 3, 5, and 10 min. Color (ADMI) decreased rapidly in the first minutes: >65% removal at 5 min for 100 mg/L H2O2, and a maximum of 76% at 10 min for 333 mg/L H2O2. Linearized kinetic fits showed that a pseudo-second-order model (R2≈0.953-0.966) described the data better than pseudo-first-order (R2≈0.909-0.921), indicating apparent bimolecular behavior under the tested conditions. A screening-level reagent cost based on commercial 50% w/w H2O2 pricing was 5.8 THB/m3 at 100 mg/L (≈0.179 USD/m3 using 32.4 THB: USD). These results demonstrate that a household-scale UV/H2O2 configuration can provide fast decolorization of municipal secondary effluent under short contact times, with a simple kinetic descriptor and an initial cost benchmark relevant to building-level non-potable reuse.